2015
DOI: 10.1016/j.biortech.2015.01.062
|View full text |Cite
|
Sign up to set email alerts
|

A proposed aerobic granules size development scheme for aerobic granulation process

Abstract: Aerobic granulation is increasingly used in wastewater treatment due to its unique physical properties and microbial functionalities. Granule size defines the physical properties of granules based on biomass accumulation. This study aims to determine the profile of size development under two physicochemical conditions. Two identical bioreactors namely Rnp and Rp were operated under non-phototrophic and phototrophic conditions, respectively. An illustrative scheme was developed to comprehend the mechanism of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…This result was almost similar to the results obtained by Dahalan et al 33 where granulation started after the 19th day at a slower rate in the SBR reactor fed with synthetic wastewater (COD-1600 mg/L).…”
Section: Seed Sludge and Characteristics Of Wastewatersupporting
confidence: 91%
“…This result was almost similar to the results obtained by Dahalan et al 33 where granulation started after the 19th day at a slower rate in the SBR reactor fed with synthetic wastewater (COD-1600 mg/L).…”
Section: Seed Sludge and Characteristics Of Wastewatersupporting
confidence: 91%
“…Previous studies on other granular biotechnologies, such as aerobic granular sludge, showed that the structure of granules changes as the granules grow larger. Changes in size and structure influence mass transfer in granules, further causing changes in ecology, physiology, as well as physicochemical properties of granules. Hence, granule size is directly related with the characteristics and functions of granules and ultimately determines the performance of bioprocesses. Although the growth of photogranules in size is obvious in OPG reactor operation, ,, the structural as well as community changes along with size progression remain mainly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Dried granule was then sputter-coated with gold particles before analyzed under SEM. The mineral composition analysis was performed by scanning electron microscope coupled with energy disperse X-ray spectroscopy (SEM-EDX) (Zeiss Supra 35VP, Germany) equipped with a microprobe Kevex and image capture and management system Rontec E-500 (Rontgeanalysen, Technik) according to Benitez et al (2005) and Dahalan et al (2015). The mineral composition was quantified in atomic percentage of every component by using FEI QUANTA 200 with EDX-system.…”
Section: Methodsmentioning
confidence: 99%